Technical note: A new online tool for δ18O–temperature conversions - D. E. Gaskell; P. M. Hull (Climate of the Past, 2023)
The stable-oxygen-isotopic composition of marine carbonates (δ18Oc) is one of the oldest and most widely used paleothermometers. However, interpretation of these data is complicated by the necessity of knowing the δ18O of the source seawater (δ18Ow) from which CaCO3 is precipitated. The effect of local hydrography (the “salinity effect”) is particularly difficult to correct for and may lead to errors of >10 ∘C in sea-surface temperatures if neglected. A variety of methods for calculating δ18Ow have been developed in the literature, but not all are readily accessible to workers. Likewise, temperature estimates are sensitive to a range of other calibration choices (such as calibration species and the inclusion or exclusion of carbonate ion effects), which can require significant effort to intercompare. We present an online tool for δ18O–temperature conversions which provides convenient access to a wide range of calibrations and methods from the literature. Our tool provides a convenient way for workers to examine the effects of alternate calibration and correction procedures on their δ18O-based temperature estimates.